Pengenalan dan Penguasaan Kosakata Bahasa Inggris dengan Media Boneka Jari pada Komunitas Anak-anak - Alfiqri, Aqsa Fadilah; Widiastuty, Hesty; Harahap, Alya Rohali; Yuvia, Yuvia (Kifah: Jurnal Pengabdian Masyarakat, 2023)
This community service develops the role of Boneka Jari in helping elementary school children in the Temanggung Kenyapi complex to improve their English vocabulary through understanding and memorizing. This PkM method uses the Service Learning methodology. Boneka Jari in the form of animals are used as tools that attract children's attention and help them understand English vocabulary related to animals. These dolls also facilitate the memorization process. During the service, the children were involved in learning sessions involving finger puppets. They interact with Boneka Jari and learn English vocabulary related to animals through dialogue and games. Children are given the opportunity to memorize vocabulary with the help of Boneka Jari. Evaluations show significant improvements in understanding and memorizing vocabulary, as well as increased confidence in using new vocabulary in everyday conversations. These findings indicate that the use of Boneka Jari is effective in helping children learn English vocabulary. This approach can be applied in various contexts and provides benefits in language development in the Temanggung Kenyapi complex and beyond.